Effects of continuous and pulse irrigation with different nitrogen applications on soil moisture, nitrogen transport and accumulation in root systems - Huang, Lingmiao; Yang, Peiling; Ren, Shumei; Cui, Haobo (International Journal of Agricultural and Biological Engineering, 2018)
Pulse and continuous irrigation can affect water distribution in the soil, thereby affecting the growth and distribution of root systems. Different base and topdressing fertilizers can affect nitrogen transport in the soil and root distribution, thus affecting root water and nitrogen uptake. This study used pot experiments to set up four different nitrogen levels, including two different irrigation methods, to research the effects of soil moisture, nitrogen transport, nitrogen accumulation and root systems under the conditions of continuous and pulse irrigation, as well as different nitrogen applications. Result showed that continuous irrigation can increase the moisture content around the drip emitter position and reduce the soil moisture content in the horizontal spreading compared with pulse irrigation, especially reducing the horizontal spreading in the deep soil layers. One treatment in this study did not apply base fertilizer, and then supply topdressing fertilizer at a ratio of 2:4:4 in the seedling stage, jointing stage and tasseling stage, respectively. This treatment is beneficial for improving nitrogen utilization efficiency. Furthermore, this treatment can increase the root length density and root surface area in the deep soil layers, especially in the 20-35 cm soil depth, and to some extent increase the deep growth of the root system. Keywords: pulse irrigation, continuous irrigation, fertilization, irrigation, soil DOI: 10.25165/j.ijabe.20181105.3674 Citation: Huang L M, Yang P L, Ren S M, Cui H B. Effects of continuous and pulse irrigation with different nitrogen applications on soil moisture, nitrogen transport and accumulation in root systems. Int J Agric & Biol Eng, 2018; 11(5): 139–149.